Mesenchymal chondrosarcoma: Prognostic factors and outcome in 113 patients. A European Musculoskeletal Oncology Society study. Issue 3 (February 2015) - Frezza, Anna Maria; Cesari, Marilena; Baumhoer, Daniel; Biau, David; Bielack, Stephen; Campanacci, Domenico Andrea; Casanova, José; Esler, Claire; Ferrari, Stefano; Funovics, Philipp T.; Gerrand, Craig; Grimer, Robert; et al.
Abstract Background Mesenchymal chondrosarcoma (MCS) is a distinct, very rare sarcoma with little evidence supporting treatment recommendations. Patients and methods Specialist centres collaborated to report prognostic factors and outcome for 113 patients. Results Median age was 30 years (range: 11–80), male/female ratio 1.1. Primary sites were extremities (40%), trunk (47%) and head and neck (13%), 41 arising primarily in soft tissue. Seventeen patients had metastases at diagnosis. Mean follow-up was 14.9 years (range: 1–34), median overall survival (OS) 17 years (95% confidence interval (CI): 10.3–28.6). Ninety-five of 96 patients with localised disease underwent surgery, 54 additionally received combination chemotherapy. Sixty-five of 95 patients are alive and 45 progression-free (5 local recurrence, 34 distant metastases, 11 combined). Median progression-free survival (PFS) and OS were 7 (95% CI: 3.03–10.96) and 20 (95% CI: 12.63–27.36) years respectively. Chemotherapy administration in patients with localised disease was associated with reduced risk of recurrence (P = 0.046; hazard ratio (HR) = 0.482 95% CI: 0.213–0.996) and death (P = 0.004; HR = 0.445 95% CI: 0.256–0.774). Clear resection margins predicted less frequent local recurrence (2% versus 27%; P = 0.002). Primary site and origin did not influence survival. The absence of metastases at diagnosis was associated with a significantly better outcome (P < 0.0001). Data on radiotherapy indications, dose and fractionation were insufficiently complete, to allow comment of its impact on outcomes. Median OS for patients with metastases at presentation was 3 years (95% CI: 0–4.25). Conclusions Prognosis in MCS varies considerably. Metastatic disease at diagnosis has the strongest impact on survival. Complete resection and adjuvant chemotherapy should be considered as standard of care for localised disease.